2021
DOI: 10.1167/iovs.62.3.38
|View full text |Cite
|
Sign up to set email alerts
|

Isorhamnetin Ameliorates Aspergillus fumigatus Keratitis by Reducing Fungal Load, Inhibiting Pattern-Recognition Receptors and Inflammatory Cytokines

Abstract: Isorhamnetin is a natural flavonoid with both antimicrobial and antiinflammatory properties, but its effect on fungal keratitis (FK) remains unknown. The current study aims to investigate the antifungal and anti-inflammatory effects of isorhamnetin against mouse Aspergillus fumigatus keratitis. METHODS.In vitro, the lowest effective concentration of isorhamnetin was assessed by minimum inhibitory concentration and cytotoxicity tests in human corneal epithelial cells (HCECs) and RAW264.7 cells. The antifungal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Licochalcone A can delay the progression of inflammation by inhibiting the inflammatory response and inhibiting the degradation of cartilage matrix [ 33 ]. As a direct derivative of quercetin, isorhamnetin has good anti-inflammatory, antioxidant, and antiallergic effects [ 34 , 35 ]. Experiments show that isorhamnetin can inhibit the NF- k B signaling pathway, inhibit the release of cytokines (TNF-a, IL-6, IL-1B), and alleviate inflammation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Licochalcone A can delay the progression of inflammation by inhibiting the inflammatory response and inhibiting the degradation of cartilage matrix [ 33 ]. As a direct derivative of quercetin, isorhamnetin has good anti-inflammatory, antioxidant, and antiallergic effects [ 34 , 35 ]. Experiments show that isorhamnetin can inhibit the NF- k B signaling pathway, inhibit the release of cytokines (TNF-a, IL-6, IL-1B), and alleviate inflammation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al found that HK could down-regulate the inflammatory response mediated by LPS through inhibiting the expression level of TNF-α and IL-6 in primary human keratinocytes(48). Our data indicated that HK also significantly down-regulated the mRNA and protein levels of corneal pro-inflammatory cytokines TNF-α, IL-6, and IL-1β, which could mediate the recruitment, activation and adhesion of neutrophils(49). A plentiful supply of virulence factors produced by the inflammatory cascade can damage the corneal epithelium and corneal stromal structure(50, 51).…”
Section: Discussionmentioning
confidence: 81%
“…[29][30][31] The lack of high-efficiency, lowtoxicity, and high-permeability drugs for corneal fungal infections means poor prognosis. [32][33][34] Nanobodies that naturally lack light chains are unique antibodies first found in the sera of sharks and camelids. 35 Because they possess many desirable attributes, such as small molecules, low immunogenicity, strong penetration, and high binding affinity, different types nanobodies have become novel diagnosis and treatment methods for tumors and infectious diseases.…”
Section: Discussionmentioning
confidence: 99%